General Guidelines for Managing Pastures for Dairy Cows - Lynn E. Sollenberger; Yoana C. Newman; Joao M. B. Vendramini (EDIS, 2009)
Revised! SS-AGR-94, a 4-page illustrated fact sheet by L. E. Sollenberger, Y. C. Newman, and J. M. B. Vendramini, is part of the Florida Forage Handbook. It answers dairy producers’ questions about managing pasture as a major source of nutrients for milking cows — soil testing and pasture fertilization, choice of forage species, and grazing strategies. Published by the UF Department of Agronomy, June 2009.